Preliminary results on epidemiology of Coconut Lethal Yellowing in Ghana - Bonnot François (Oléagineux, Corps gras, Lipides, 2009)
Epidemiological studies are of major importance in understanding the determinants of plant diseases in order to control the risks of their spreading. A research programme on the epidemiology of coconut lethal yellowing, or Cape Saint Paul Wilt Disease (CSPWD), in Ghana was launched in March 2007. The objective was to characterize the distribution and spread of the disease in space and time at various scales, and their relation with the environment. This article presents the general strategy used to evaluate the incidence of CSPWD along with the environmental, ecological and agronomical variables at regional level. A survey was undertaken on 1,166 plots of Coconut Sector Development Project (CSDP) planted with Malayan Yellow Dwarf (MYD) × Vanuatu Tall (VTT) hybrids in Western Region and Central Region. Preliminary results on the distribution of CSPWD and outside variables at regional scale, along with their relations, are given.